Asystole after Orthotopic Lung Transplantation: Examining the Interaction of Cardiac Denervation and Dexmedetomidine. (8th October 2012) - Webb, Christopher Allen-John; Weyker, Paul David; Flynn, Brigid Colleen
Abstract : Dexmedetomidine is an α 2 -receptor agonist commonly used for sedation and analgesia in ICU patients. Dexmedetomidine is known to provide sympatholysis and also to have direct atrioventricular and sinoatrial node inhibitory effects. In rare instances, orthotopic lung transplantation has been associated with disruption of autonomic innervation of the heart. The combination of this autonomic disruption and dexmedetomidine may be associated with severe bradycardia and/or asystole. Since orthotopic lung transplant patients with parasympathetic denervation will not respond with increased heart rate to anticholinergic therapy, bradyarrhythmias must be recognized and promptly treated with direct acting beta agonists to avoid asystolic cardiac events.